Challenges and Opportunities in Heritage Conservation and Tourism Development: A Case Study of Jagdishpur (Formerly Islamnagar), Madhya Pradesh, India - Vishal Chettry
Heritage sites frequently serve as icons of the city, despite having undergone numerous social and aesthetic transformations. The conservation efforts of the heritage sites ensure the preservation of original and indigenous characteristics. Jagdishpur, formerly Islamnagar is a fortified complex with a blend of historical narratives and architectural richness has marked a significant stint as the erstwhile capital of the Bhopal princely state. Despite its profound potential for heritage tourism, Jagdishpur, now located on the outskirts of contemporary Bhopal city, experiences low visitor footfall. Therefore, this study attempts to identify the challenges present within the current tourism infrastructure through site visits, visual survey techniques and primary survey. It assesses the physical condition of heritage structures, surrounding natural resources, and existing infrastructure while exploring nearby potential tourist attractions. The results highlight the deteriorating condition of key structures such as Rani Mahal, Chaman Mahal, and Gaund Mahal, alongside the crumbling fortification walls, all of which require urgent conservation efforts. Additionally, the absence of basic amenities during events like the Ijitima fair and encroachment near heritage sites intensifies these challenges. The study offers strategies for city planning officials to address heritage conservation and support community development.